Педагогічні умови розвитку соціального інтелекту дошкільників - Давиденко, Людмила Миколаївна (My University, 2020)
Тема магістерської роботи «Педагогічні умови розвитку соціального інтелекту дошкільників» досліджувалася на теоретичному та емпіричному рівнях. Результати вивчення представлені у трьох розділах роботи. На теоретичному рівні обґрунтована проблема необхідність розвитку соціального інтелекту дошкільників, зокрема: проаналізовано стан вивчення проблеми розвитку феномену у дошкільників у психолого-педагогічних дослідженнях; здійснено огляд та відповідну аналітичну роботу над джерельною базою з вивчення проблеми розвитку соціального інтелекту дітей дошкільного віку. Для розв’язання емпіричних завдань дослідження, розроблена програма й методика констатувального, формувального й контрольного етапів педагогічного експерименту. Розроблені критерії, показники та рівні сформованості знань і вмінь вихователів щодо розвитку соціального інтелекту на основі виділених обґрунтованих педагогічних умов.
The theme of the master's thesis "Pedagogical conditions for the development of social intelligence of preschool children" was studied at the theoretical and empirical levels. The results of the study are presented in three sections of the paper. At the theoretical level, the problem of the need to develop the social intelligence of preschool children is substantiated, in particular: the state of studying the problem of the development of the phenomenon in preschool children in psychological and pedagogical research is analyzed; a review and corresponding analytical work on the source base for studying the problem of the development of social intelligence of preschool children is carried out. To solve the empirical problems of the study, a program and methodology of the ascertaining, forming and control stages of the pedagogical experiment have been developed. Criteria, indicators and levels of formation of knowledge and skills of educators for the development of social intelligence are developed on the basis of the identified reasonable pedagogical conditions.
Keywords: соціальний інтелект; соціальний інтелект дитини